High-Resolution Spectral Domain-Optical Coherence Tomography in Multiple Sclerosis, Part II – the Total Macular Volume. The First Follow-Up Study over 2 Years - Serbecic, Nermin; Aboul-Enein, Fahmy; Beutelspacher, Sven; Khan, Adnan; Vass, Clemens; Kristoferitsch, Wolfgang; Reitner, Andreas; Schmidt-Erfurth, Ursula (Frontiers in Neurology, 2014)
Background: To date, the results of studies investigating the use of optical coherence tomography (OCT) in multiple sclerosis (MS) patients seem to be preliminary, and at times contradictory. Reasons for this include the incompletely understood aetiology and heterogeneity of MS, the physiological variations of the retinal nerve fibre layer (RNFL) or total macular volume (TMV), and limitations in methodology. Firstly, it remains to be discovered whether any retinal changes develop in a stepwise fashion or continuously, and if so, whether these occur in all MS patients or a subset. Secondly, as any hypothesized retinal changes are likely to be subtle, newly available high resolution spectral domain OCT devices (SD-OCT) will be prerequisite. Thirdly, cross-sectional studies can never replace longitudinal studies to determine changes over time and extrapolation must be avoided. Additionally, if the hypothesis is correct, then retinal and global brain tissue changes must be detected in a substantial majority of MS patients, and they should correlate strictly with each other. Furthermore, detection should be possible in MS patients with a high degree of disease activity and/or long disease course. Methodology: Thirty-seven MS patients (relapsing remitting, n=27; secondary progressive, n=10) were examined prospectively on two occasions with a median interval of 22.4±0.5 months [range 19-27]. We used SD-OCT with the Spectralis 3.5mm circle scan protocol with locked reference images and eye tracking mode. None of the patients had an optic neuritis 12 months prior to study entry or during the observation period. Principal Findings: The initial TMV pattern differed between study participants, but was found unchanged over 2-year observation period despite high disease activity or long disease course. The TMV correlated well with the RNFL. Conclusions: The significance of differences in TMV- (and RNFL-) between study participants remains unclear. Until these differences h